Qualitative and quantitative analysis of extracellular polymeric substances in partial nitrification and full nitrification reactors. (September 2017) - Wei, Dong; Yan, Tao; Zhang, Keyi; Chen, Ya; Wu, Na; Du, Bin; Wei, Qin
Graphical abstract: Highlights: Partial nitrification reactor was achieved by using low DO strategy. Higher TN removal efficiency was observed in partial nitrification reactor. EEM showed fluorescence property of LB-EPS and TB-EPS from two reactors. TB-EPS exhibited a greater number of molecular weight fractions. Abstract: In present study, two column-type sequencing batch reactors with alternative anoxic/aerobic phases were operated and compared under partial nitrification and full nitrification modes by controlling different dissolved oxygen (DO) conditions. During steady state, the characterizations of extracellular polymeric substances (EPS) from two reactors were qualitatively and quantitatively analyzed through chemical and spectroscopic approaches. Data implied that partial nitrification reactor had relatively higher total nitrogen (TN) removal efficiency and loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS) contents. According to excitation emission matrix (EEM) spectra, LB-EPS and TB-EPS from two kinds of reactors expressed similar fluorescence peak locations but different intensities. Fluorescence regional integration (FRI) further suggested that Region IV was the main fraction in both types of EPS fractions. Moreover, TB-EPS exhibited a greater number of molecular weight fractions than those of LB-EPS. Both EPS fractions had similar functional groups, which represented the complex nature of EPS compositions.